Distribution of Pediatric Surgical Cases Over Five Years in a Tertiary Hospital - Laila, Kamrun; Khan, Mohammad Asif; Dasgupta, Pritam; Ali, Sytuha Binta; Hossain, Kamrul (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Health care providers have given their efforts to reduce the rate of child mortality and morbidity, throughout the world. But inadequate amount of knowledge about the demand of pediatric surgical care lagging us behind to achieve our goal. The study was conducted to observe the distribution of pediatric surgical cases over five years in the study site. Materials and methods: It was a descriptive type of observational study. Data was extracted from record book of surgical procedures done in Department of Pediatric Surgery, Bangabandhu Memorial Hospital (BBMH) Chattogram, over a period of 5 years, from January 2013 to December 2017. Written permission was taken from the hospital authority prior to data collection. Descriptive data analysis was done by Microsoft Excel (Version 2013). Results: Out of total 2977 cases, 10-15 years age group had a predominance of 828 cases and the least was more than 15 years age group (672 cases). A male predominance was observed, with 65% of all cases (Total- 1935 cases) while female patients comprised rest of it. Male female ratio was 1.86: 1. Over 5 years period appendicectomy (497) circumcision (530) herniotomy (425) rectal polypectomy (255) showed abundant number covering majority of the surgical procedures. On the contrary, splenectomy with cholecystectomy was the least performed surgery (5) mostly done for haemolytic disease of newborn (Thalassemia). Conclusion: To deal with huge amount of surgical patients of pediatric age group an organized effort is required to ensure proper environment and resources to facilitate optimal implementation of surgical care to the future generations of a country. JCMCTA 2018 ; 29 (2) : 47-52